Built Environmental Correlates of Cycling Accidents Involving Fatalities and Serious Injuries in London, UK - Labetski, Anna; Chum, Antony (Frontiers in Sustainable Cities, 2020)
Introduction: Approximately 2552 individuals were killed or seriously injured through cycling accidents in the Greater London Area between 2010-2015. The purpose of this study is to investigate a wide range of built environmental correlates of cycling accidents resulting in KSI so that we can identify potential areas for targeted interventions. Methods: We performed a cross-sectional analysis to examine the association between serious cycling injuries (2010-15), using road segment as the unit of analysis, and a wide range of built environmental characteristics. Multilevel models were used to account for potential spatial clustering. Results: Serious cycling injuries were independently associated with higher commercial and residential densities, higher distance to speed camera, higher bus, car, and 2-wheeled (motorcycle and moped) traffic, and higher density of alcohol outlets. Greenspace was associated with decreased odds of injuries up to the 3rd quartile, but roads adjacent to the highest levels of green space (4th quartile) had increased odds of injuries. Findings from our study point to the potential of urban planning interventions to reduce serious cycling injuries (e.g. speed cameras, improving safety near alcohol outlets and in parks and recreational areas, etc.). Further research using quasi-experimental approaches is required to evaluate whether the implementation of interventions leads to injury reductions.